Empowering Local Health Systems through Digital Financial Inclusion: A Qualitative Study of North Sumatra’s Community Clinics - Thomas Sheku Marah (JUSTICES: Journal of Law, 2026)
The research examines how digital financial inclusion strengthens local health systems in North Sumatra through its effects on community health clinic accessibility, and operational efficiency, and sustainability of puskesmas and independent clinics. A qualitative research method enables this study to explore financial innovation effects on healthcare delivery through interviews and field observations with health administrators, and local fintech actors, and OJK-affiliated institutions. The research will identify how mobile payment systems and microfinancing, and digital banking platforms operate to maintain business operations and support healthcare funding at the community level. The research identifies three main barriers to financial innovation in healthcare which include digital literacy issues and regulatory challenges. Inadequate infrastructure while suggesting practical solutions for OJK and regional governments to enhance financial innovation in healthcare. The paper supports Indonesia's Sustainable Development Vision 2045 by presenting policy discussions which unite financial access with regional health system development.